Penggunaan Multimedia Berbasis Power Point Interaktif untuk Meningkatkan Hasil Belajar Tema 9 Subtema 1 di Kelas V SD Negeri 71 Banda Aceh - Yara Dwi Husna; Intan Safiah; Sulaiman Sulaiman (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
The aim of this research is to find out how the activities and improvement of student learning outcomes by using interactive PowerPoint on Single and Mixed Substances topic in 5th grade of SD Negeri 71 Banda Aceh. The hypothesis that the researcher proposes is that the use of interactive PowerPoint can increase the activity and learning outcomes of students on Single and Mixed Substances topics. The approach used is a qualitative approach with classroom action research. Data collection methods, namely observation, and test. Meanwhile, to analyze the data, the researcher explained thoroughly the conditions in the field and the result of the cycle evaluation. The results showed that the activity of students in the first cycle was in sufficient criteria while the second cycle was in very good criteria. The average value of pre-cycle students is 54,1 with classical completion of 20%. Cycle I became 67,4 with classical completion of 51% and cycle II an average value of 82,9 with classical completion of 92%. The conclusion of the study is that the use of interactive power point-based multimedia can improve learning outcomes for Theme ( Sub-theme 1 with Single and Mixed Substances in 5th grade of SD Negeri 71 Banda Aceh